Pendekatan Skill Time Tehnik Dasar Passing Sepakbola Pada Kelas 1 SD Islamiyah Pontianak - Atiq, Ahmad (Universitas Negeri Semarang, 2013)
Physical education is an education that is geared towards the development of human motion as a whole and therefore the need for special attention and continuous, in this era of education itself should never be made arbitrarily without any firm and clear concepts, many teachers in the learning process experienced problems such as not looking at the characteristics of students who are facing conditions that is where the actual students need to move freely liluasan but the fact that students feel pressured irregular movement patterns are not conveyed by skill learning approach therefore time is the right solution in the process dariyang easy steps towards a difficult or from leading to the complex simple, the results are still having difficulty teryata approach in conducting basic technique passing the ball in the leg.